Pelatihan Pengenalan Teknologi san Digitalisasi untuk Bisnis UMKM - Prasetyo, Johan Hendri; Fabrianto, Luky; Wiharso, Gani; Puspita, Ratna (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
In today’s fast-paced digital era, MSMEs in Bekasi City face significant challenges in integrating digital technology into their business operations. Many lack the knowledge and skills needed to adopt technology effectively, making them vulnerable to competitive disadvantages, limited market expansion, and exposure to digital security threats. To address these issues, comprehensive digital literacy training is essential to empower MSME actors to utilize technology in a safe and efficient manner that supports business growth. The